2014
DOI: 10.1186/1556-276x-9-103
|View full text |Cite
|
Sign up to set email alerts
|

Catechin-capped gold nanoparticles: green synthesis, characterization, and catalytic activity toward 4-nitrophenol reduction

Abstract: An eco-friendly approach is described for the green synthesis of gold nanoparticles using catechin as a reducing and capping agent. The reaction occurred at room temperature within 1 h without the use of any external energy and an excellent yield (99%) was obtained, as determined by inductively coupled plasma mass spectrometry. Various shapes of gold nanoparticles with an estimated diameter of 16.6 nm were green-synthesized. Notably, the capping of freshly synthesized gold nanoparticles by catechin was clearly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 25 publications
(23 reference statements)
3
28
0
Order By: Relevance
“…Significantly, PAGNPs2 exhibits an excellent catalytic degradation of 4-NP by converting it to 4-AP within 5 min, and this improved catalytic efficacy can be correlated with its particle size. Comparing this catalytic potential of the PAGNPs2 sample with previous reports, there is a report that nanocrystalsupported gold nanoparticles caused the degradation of 4-NP in 14 min (Wu et al, 2014) and, in another study, catechincapped gold nanoparticles have been reported to exhibit the same degradation activity in 30 min (Choi et al, 2014), while our PAGNPs2 sample exhibits better catalytic degradation within 5 min.…”
Section: Catalysissupporting
confidence: 82%
“…Significantly, PAGNPs2 exhibits an excellent catalytic degradation of 4-NP by converting it to 4-AP within 5 min, and this improved catalytic efficacy can be correlated with its particle size. Comparing this catalytic potential of the PAGNPs2 sample with previous reports, there is a report that nanocrystalsupported gold nanoparticles caused the degradation of 4-NP in 14 min (Wu et al, 2014) and, in another study, catechincapped gold nanoparticles have been reported to exhibit the same degradation activity in 30 min (Choi et al, 2014), while our PAGNPs2 sample exhibits better catalytic degradation within 5 min.…”
Section: Catalysissupporting
confidence: 82%
“…Comparing to the extracellular green‐synthesized metallic NPs, the rate constant on ( Pd@Ag ) @Sp ‐5 composites prepared in this study was 66‐fold higher than that of bio‐PdPt NPs (0.0316 min −1 ), 21‐fold higher than of the catechin‐AuNPs (0.091 min −1 ), and 5‐fold higher than that of colloidal protein–Ag NPs (0.39 min −1 ) . In the case of the green biosynthesis method, colloidal stability of metallic NPs is usually ensured through adsorption of biopolymers or biomolecules onto their surface, such as expolysaccharides, proteins, and catechins, which may be disadvantageous for their better catalytic performance. But the Pd@Ag NPs in this research are polymer free because they are electroless deposited, which contributes to the higher catalytic activity.…”
Section: Resultsmentioning
confidence: 77%
“…)0.075 (2.22 equiv. )[28]7 Bupleurum falcatum root extract10.5 ± 2.3Spherical0.82 × 10 -3 0.077 (100 equiv. )0.1 (1.43 equiv.…”
Section: Resultsmentioning
confidence: 99%